PENGARUH EDUKASI FOOD WASTE TERHADAP PENGETAHUAN MURID MADRASAH IBTIDAIYAH PONDOK KARYA PEMBANGUNAN DENGAN MEDIA POSTER DAN VIDEO TAHUN 2023 - Citra Risky Alifah (2023)
Food waste is still one of the problems that could not be properly resolved. Lack of public knowledge about food waste caused them did not know the impact that will occur if the number of food waste increased. The study aims to determine the effect of food waste education on student's knowledge at Madrasah Ibtidaiyah Pondok Karya Pembangunan which was conducted from May until June 2023. This research used a quasi-experimental method with a pretest-posttest two group design with poster and video media with data analysis using the Cox Regression Test. The samples were selected by purposive sampling technique with total of 66 students at Madrasah Ibtidaiyah Pondok Karya Pembangunan. The research samples were divided into two groups, there were the poster experiment group and the video control group. The test results show that there has been a change in the level of knowledge before and after food waste education in Madrasah Ibtidaiyah Pondok Karya Pembangunan students using posters RR 1,67, CI 95% (0,39-6,97) and video media RR 1. Poster media was more effective in increasing knowledge when compared to video media.